1998
DOI: 10.1152/ajplung.1998.275.2.l365
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor mRNA expression is upregulated in bleomycin-induced lung fibrosis

Abstract: Connective tissue growth factor (CTGF) is a newly described 38-kDa peptide mitogen for fibroblasts and a promoter of connective tissue deposition in the skin. The CTGF gene promotor contains a transforming growth factor-β1 (TGF-β1) response element. Because TGF-β1 expression is upregulated in several models of fibroproliferative lung disease, we asked whether CTGF is also upregulated in a murine lung fibrosis model and whether CTGF could mediate some of the fibrogenic effects associated with TGF-β1. A portion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
155
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(168 citation statements)
references
References 20 publications
11
155
0
2
Order By: Relevance
“…This may be the reason why we found an association between VEGF expression and von Willebrand factor in this model in contrast to the results of Fehrenbach et al Recently, Inoki et al (22) demonstrated that connective tissue growth factor (CTGF) binds to VEGF and inhibits VEGF-induced angiogenesis. CTGF and VEGF are downstream effectors of TGF-␤, and these growth factors are known to be up-regulated in this model (23). At the advanced phase of fibrosis at 28 days, angiogenesis may be effected by other factors such as CTGF.…”
Section: Discussionmentioning
confidence: 84%
“…This may be the reason why we found an association between VEGF expression and von Willebrand factor in this model in contrast to the results of Fehrenbach et al Recently, Inoki et al (22) demonstrated that connective tissue growth factor (CTGF) binds to VEGF and inhibits VEGF-induced angiogenesis. CTGF and VEGF are downstream effectors of TGF-␤, and these growth factors are known to be up-regulated in this model (23). At the advanced phase of fibrosis at 28 days, angiogenesis may be effected by other factors such as CTGF.…”
Section: Discussionmentioning
confidence: 84%
“…There, CTGF can stimulate fibroblast proliferation in an autocrine and paracrine manner as has been suggested with other models. 31 As with TGF-␤1, CTGF was further noted in allografts from Smad3-deficient recipients. Together with others' findings in cultured Smad3-deficient fibroblasts showing no increased production of CTGF after treatment with TGF-␤1, 14 we conclude that this up-regulation in experimental OB is independent not only of Smad3, but of TGF-␤1 itself.…”
Section: Discussionmentioning
confidence: 94%
“…The fibroblasts present in bleomycin-induced fibrotic lesions show activated Smad3 (21), and bleomycin-induced lung fibrosis is reversed by application of an adenovirus encoding Smad7 (22) and is known to be less severe in Smad3-deficient mice (23). Increased CTGF expression has been observed in this mouse model (4,6). However, the contribution of CTGF to bleomycin-induced pulmonary fibrosis and the mechanisms underlying the action of CTGF have yet to be elucidated.…”
mentioning
confidence: 91%
“…However, CTGF is consistently overexpressed in fibrotic lesions in patients with SSc and in those with other connective tissue diseases, affecting organs including the dermis, liver, kidney, heart, and lung (6,7). Elevated CTGF expression also correlates with, and contributes to, expression of ␣-smooth muscle actin (␣-SMA) and the myofibroblast phenotype in, for example, repair and development of connective tissue (8,9).…”
mentioning
confidence: 99%